TINJAUAN ETIKA BISNIS ISLAM DALAM PRODUKSI DAN PENGOLAHAN LIMBAH (STUDI KASUS PADA INDUSTRI TAHU DI DESA SIWATU ): 1. Tinjauan Etika Bisnis Islam Dalam Proses Produksi Tahu, 2. Tinjauan Etika Bisnis Islam Dalam Proses Pengolahan Limbah Tahu - Ainusshofa, Nurul Isma; Hermawan Adinugraha, Hendri; Syafi'i, M. Aris (RISTEK : Jurnal Riset, Inovasi dan Teknologi Kabupaten Batang, 2025)
The cost of tofu has continued to increase due to COVID-19, marked by a spike in soybean prices reaching IDR 13,500/kg. This can cause a decrease in the quality of the tofu produced. In addition, tofu waste is also a factor in environmental pollution. The purpose of this study is to provide a perspective on the application of Islamic business ethics in the tofu industry using a descriptive qualitative approach method based on primary and secondary data sources obtained from interviews, observations, documentation, and intuitive subjects. In this study, it was found that there are ways to apply Islamic business ethics both in production and waste processing as an alternative to reducing pollution in the surrounding environment. This contributes to driving the local economy in Batang Regency, especially in Siwatu Village.